PEMODELAN DINAMIKA STRUKTUR DAN IMPLEMENTASI AWAL KENDALI AKTIF PEREDAMAN GETARAN UNTUK WAHANA ANTARIKSA FLEKSIBEL - AGUNG, RIZQY
In this research, vibration on the spacecraft’s structure is occurs due to the spacecraft attitude and its operational condition on a certain orbit. The model of spaceraft’s solar panel is modelled by selecting the typical value of natural frequency and it’s studied by using its flexibel equation of motion. Decreasing perfomance of the solar panel due to the vibration phenomenon need to be overcome with some solution. Applying the active vibration control is one of the solution to overcome the phenomenon. Evaluation of structural dynamic on the solar panel is derived by using analytical method and it is simulated by using numerical method. The study of active vibration control is applied by evaluating the dynamic characteristic of it. The state-space function is used to formulate the linear control vibration system. By using MATLAB, the control system was modelled as controller and its characteristic (in state-space) is studied numerically. The control sistem is designed by using two method, which are Pole-Placement method and Linear Quadratic Regulator (LQR) method. As the result, the Pole-Placement method could reduce vibration in less than 0.5 t/T. Whereas, the Linear Quadratic Regulator method could reduce vibration in 0.7 to 140 t/T. The LQR method is resulting more variative time to reduce the vibration, so the system could be controlled and adjusted due to its design requirement.